Cysticercus Antigens in Cerebrospinal Fluid Samples from Patients with Neurocysticercosis - Pardini, Alessandra Xavier (American Society for Microbiology, 2001)
Antigens were detected in cerebrospinal fluid (CSF) samples from patients with neurocysticercosis (NC) by enzyme-linked immunosorbent assay (ELISA) using polyclonal sera of rabbit anti-Taenia solium cysticerci (anti-Tso) and anti- Taenia crassiceps cysticerci vesicular fluid (anti-Tcra or anti-Tcra <30 kDa). A group of NC patients (n = 174) were studied (NC), including 40 patients in different phases of the disease. ELISAs carried out with the anti-Tso, anti-Tcra, and anti-Tcra <30 kDa showed sensitivities of 81.2, 90, and 95.8% and specificities of 82, 98, and 100%, respectively. The 14- and 18-kDa low-molecular-weight peptides were only detected in CSF samples from patients with NC by immunoblotting with anti-Tso and anti-Tcra sera. Because of the importance of the diagnosis and prognosis of cysticercosis, the detection of antigens may contribute as an additional marker to the study and clarification of the parasite-host relationship.